An Analysis of Health Benefits of Bitter Melon (International Journal of Innovative Research in Engineering & Management, 2021)
Outside of traditional medicine, herbalists have a long history of  usage. Improvements in analysis and quality control, as well as  advancements in clinical research, are demonstrating usefulness of herbal medicine in the treatment and prevention of illness.  Momordicacharantia (Bitter melon) is a climbing vine whose  bitter leaves and green fruits have been used to treat cancer,  diabetes, and a variety of infectious illnesses. It's also a potent  anti-HIV/AIDS weapon. Roots, according to Ayurveda, are  beneficial in treatment of eye problems. Bitter, cooling,  digestible, laxative, antipyretic, anthelmintic, appetizer, treats  biliousness, blood disorders, anaemia, urinary discharges,  asthma, ulcers, bronchitis, and other ailments Fruit is bitter,  carminative, tonic, stomachic, aphrodisiac, anthelmintic,  astringent to intestines, and helpful in the treatment of syphilis,  rheumatism, spleen problems, and other ailments, according to  Unani school of medicine. Bitter melon is well-known for its  ability to help people with diabetes. Bitter melon contains a  molecule that is chemically similar to insulin and is often  referred to as p-insulin. Researchers have discovered that when  taken consistently over a length of time, it has the potential to  replace insulin in body. It also includes charantin, a steroidal  saponin, peptides that are related to peptides, and some alkaloids  that successfully regulate blood sugar levels.
Keywords: Bitter melon; Diabetes; Food; Medicine; Momordicacharantia